Gramsci’s appropriations for the education of people with disabilities: why the inclusive school is not the unitary school (PerCursos, 2024)
This text aims to expose the contradictions surrounding the defense that the inclusive school is equivalent to the Unitary School proposed by Gramsci (2001). The exhibition is based on the analysis of the book Gramsci and Special Education (Melo; Rafante; Gomes, 2019), in which a series of arguments are recorded that equate Special Education from an inclusive perspective with the Unitary School. For the analysis, in addition to the aforementioned book, we started from the post in Notebook 12 on the Unitary School (Gramsci, 2001). Given the authors' arguments about Special Education from an inclusive perspective and the Unitary School in Gramsci (2001), we conclude that the authors take Gramsci's contributions from a post-structuralist bias, disregarding the Marxist-Leninist theoretical-methodological basis, the analysis of the class struggle and the role of education in the fight for another model of society. Finally, we conclude that the association between the concept of Unitary School and the inclusive school is a mistake, given that the latter is not sufficient to structurally guarantee human emancipation of students from special education.
Keywords: educational politics; special education; inclusive education; Antonio Gramsci; unitary school